A Decade of Growth in Outdoor Education Research: A Bibliometric Study Based on the Scopus Database 2014–2024 - Mubarak, Husni; Fitri, Mustika (Universitas Negeri Semarang, 2024)
This study presents a comprehensive bibliometric analysis of scientific publications with the aim of identifying publication trends, citation trends, the journals with the highest number of publications, researcher tendencies, as well as network visualization, overlay mapping, and the geographical distribution of research on the topic of outdoor education. The research employed content analysis, conducted through online searches using the Scopus database and analyzed with VOSviewer software version 1.6.20. The research procedure followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) flow, including the stages of identification, screening, and eligibility assessment, covering data from 2014 to 2024. The findings indicate a year-over-year increase in publications related to outdoor education. Network visualization successfully identified several dominant topics in this domain, such as the connection between outdoor education and outdoor learning, although no linkage to psychological aspects has yet been observed. Therefore, new research opportunities may lie in integrating outdoor education with psychological studies. Overlay visualization was used to explore emerging research trends, indicated by yellow-colored terms such as outdoor learning and early childhood education. Overall, the number of scientific publications has shown significant annual growth, as has the number of article citations.